Impact of comorbidities on acute kidney injury and renal function impairment after partial and radical tumor nephrectomy. (3rd September 2021) - Wenzel, Mike; Kleimaker, Alexander; Uhlig, Annemarie; Würnschimmel, Christoph; Becker, Andreas; Yu, Hang; Meyer, Christian P.; Fisch, Margit; Chun, Felix K. H.; Leitsmann, Marianne
Abstract: Background: To test for the impact of patient comorbidities and medical risk factors on kidney function after partial (PN) or radical nephrectomy (RN) in renal cell carcinoma (RCC) patients with normal preoperative renal function. Materials and Methods: From January 2011 to December 2014, 195 consecutive RCC patients with a preoperative estimated glomerular filtration rate (eGFR) > 60 ml/min/1.73 m 2 underwent PN or RN. Stratification was performed according to postoperative acute kidney injury (AKI) vs. no AKI. Moreover, logistic regression models tested for risk factors predicting postoperative AKI and subsequent new-onset chronic kidney disease (eGFR < 60 or < 45 ml/min/1.73 m 2 ). Results: Of all eligible patients, 127 (65.1%) exhibited AKI. AKI patients underwent more frequently RN (44.9 vs. 13.2% PN) and harbored more often preoperative diabetes (17.3 vs. 5.9% no diabetes), hypertension (46.5 vs. 23.5% no hypertension) and larger median tumor size (4.5 vs. 2.5 cm, all p  < 0.05) than non-AKI patients. Moreover, after median follow-up of 14 months, 18.9% of AKI patients exhibited an eGFR < 60 ml/min/1.73 m 2 vs. 7.4% non-AKI patients ( p  = 0.01). In multivariable models, hypertension and RN were risk factors for postoperative AKI (both p  < 0.01). Age > 60 years and RN as well as preoperative diabetes were risk factors for postoperative eGFR < 60 or < 45 ml/min/1.73 m 2 (all p  < 0.05), respectively. Conclusions: Postoperative AKI is a non-negligible event especially after RN that can be further triggered by comorbidities such as diabetes and hypertension. Comorbidities should be considered in clinical decision-making for RCC surgery and patients need to be counseled about the increased risk of consecutive renal function impairment.